Науково-методичні підходи до аналізу потенціалу взаємодіючих процесів економічної системи - Гречина, І.В. (Культура народов Причерноморья, 2013)
Визначені основні складові потенціалу взаємодіючих процесів економічної системи.
Досліджені основні авторські підходи до аналізу основних елементів потенціалу взаємодіючих процесів
підприємства. Доведено, що в основні багатьох авторських методик аналізу основних складових
потенціалу взаємодіючих процесів економічної системи лежать основні напрямки фінансового аналізу
які шляхом модельного міксу можна трансформувати у методи потенціалогічного аналізу з
урахуванням принципів потенціації та модальності. Пропоновані основні етапи потенціалогічного
аналізу потенціалу взаємодіючих процесів. Определены основные составляющие потенциала взаимодействующих процессов
экономической системы. Исследованны основные авторские подходы к анализу основных элементов
потенциала взаимодействующих процессов предприятия. Доказано, что в основе большинства
авторских методик анализа основных элементов потенциала взаимодействующих процессов
экономической системы лежат основные направления финансового анализа, которые путем модельного
микса трансформируются в методы потенциалогического анализа с учетом принципов потенциации и
модальности. Предложены основные этапы потенциалогического анализа потенциала
взаимодействующих процессов. Certain basic constituents of potential of interactive processes of the economic system : economic,
technological, sociological, naturally-ecological, each of that has a row of own structural constituents, that
allows to talk about each as systems with certain subsystems. Otherwise speaking, potential of interactive
processes summarizes in itself all present resources of enterprise and source of their formation. The basic
authorial going is investigational near the analysis of basic elements of potential of interactive processes of
enterprise, namely: integration of conceptions of estimation of potential with conceptions of development of
marketing, with determination of next key indicators : volume of mine-out products, size of the fixed and
circulating assets, quantity of working, competitiveness; in quality of synthesis of resource and productive
potential with determination of specific methods and strategies of development there is symbiosis of quantitative
and quality methods.
It is well-proven that in basic many authorial methodologies of analysis of basic constituents of potential of
interactive processes of the economic system basic directions of financial analysis lie that by model mix it is
possible to transform in the methods of potential analysis taking into account principles of potent and modality.
Expediency of transformation of basic methods of methodologies of financial analysis is well-proven and
wavelet to the analysis to the requirements of potential analysis. Offered basic stages of potential analysis of
potential of interactive processes.